Coherent perfect loss with single and broadband resonators at photonic crystal nanobeam - Choi Jihoon; Hong Young Ki; Noh Heeso (Nanophotonics, 2024)
Coherent perfect absorption (CPA) has been studied in various fields, such as metasurface, photonics, and acoustics, because of its ability to perfectly absorb light at a specific wavelength. However, the narrow bandwidth of CPA makes its application to on-chip photonics challenging. This limitation can be overcome by using a broadband resonator. Here, we demonstrate the coherent perfect loss (CPL) with respect to a single and broadband resonator at photonic crystal nanobeam. By using the finite element method, both cases of the CPL were simulated and optimized for the single and broadband resonators. In the optimized structure, a CPL occurs for both resonators. These results confirm that the perfect loss region for the broadband resonator is wider than that for the single resonator. These results are experimentally verified by fabricating both cases of CPL cases on a silicon-on-insulator by using electron beam lithography. An almost perfect loss of more than 95 % is observed for both single and broadband CPLs. Furthermore, the almost perfect loss region at the broadband resonator broadens more than that at the single resonator. The optimized structure for CPL has the potential for easy applications to on-chip photonics, such as optical switches, modulators, sensors, and logic gates.